Avaliação do emprego de componentes COTS (Commercial-Off-The-Shelf) em sistemas digitais operativos - Vieira, Marco Antonio da Costa (2007)
The present work intends to analyse the use of COTS (Commercial-Off-The-Shelf) components in the development, integration, maintenance and operation of Operational Digital Systems (ODS), on military applications at the Brazilian Navy environment. This evaluation was made with the use of case studies of two systems developed by Brazilian Navy. The data used was obtained from data bases, administrative and technical reports and surveys and interviews with the personnel who has worked in the development, integration, operation and basic maintenance. For better comprehension, a bibliographic research was made about the experiences of other developers and/or operators of ODS, with COTS components, to verify if their experiences have also happened within the Brazilian Navy environment.